Validity and reliability of Nike + Fuelband for estimating physical activity energy expenditure - Tucker, W. J.; Bhammar, D. M.; Sawyer, B. J.; Buman, M. P.; Gaesser, G. A. (BMC Sports Science, Medicine and Rehabilitation, 2015)
Background